Evaluation of the knee laxities of wrestlers - Ulkar, B.; Kunduracioglu, B. (Biology of Sport, 2008)
Anterior tibial displacements of 78 elite wrestlers (20.7±3.1 years of age), 49 of them wrestling in Greco-Roman and 29 in free style, having no history of serious knee injury were measured by KT1000 (MEDmetric, San Diego, California) arthrometer. The "support leg" was deflned to be the lower extremity used for lifting up the Opponent wrestler. All the tests revealed higher displacement values in support legs of all the wrestlers (p<0.001), while no significant differences were found between the support legs and the other legs of the wrestlers of two different styles (p>0.05). The increased laxity of the support legs ie., the knees sustaining chronic overloading, may have been indicating that there are degenerative changes of the ligamentous structures, especially of the anterior cruciate ligaments. Since many studies revealed the proofs of proprioceptive deficits in anterior cruciate deficient knees, possibly there may be an impairment of these functions in uninjured but looser knees. Although there is lack of certain information concerning this issue yet, it will be better to add proprioceptive exercises to the training programs to reduce the incidence of injuries.